Spectrum sharing in frequency‐selective unlicensed bands: a game theoretic approach. Issue 4 (29th January 2012) - Xu, Yunjian; Chen, Wei; Cao, Zhigang
ABSTRACT Power allocation is an important issue for spectrum sharing of unlicensed bands, in which multiple unlicensed systems may coexist and operate. Some recent works have been reported on spectrum sharing in frequency‐flat (FF) unlicensed bands. However, there has not been much work on power allocation for spectrum sharing in frequency‐selective (FS) unlicensed bands. For multiple cooperative systems cooperating on FS interference channels (ICs), we study an optimal power allocation strategy, which allows the transmission power density to vary within one subcarrier. By showing the duality of FS and parallel FF channels, we can therefore compute the achievable rate region of the proposed strategy when systems cooperate with each other. For non‐cooperative scenarios, we construct a game‐theoretical framework for multiple selfish systems on FS ICs. This framework enables us to utilize existing protocols designed for FF ICs to FS scenarios. By numerical results, in both cooperative and non‐cooperative scenarios, we show that the proposed strategy achieves a larger rate region than a conventional strategy, where the transmission power density on each subcarrier is set equal. Our work can be regarded as an extension of previous works for FF scenarios. Copyright © 2012 John Wiley & Sons, Ltd.